Molecular dynamics simulations of the interactions between plant antimicrobial peptides and lipid membranes - Lim, Melvin Wei Sheng (2017)
Knottin-type peptides constitute the largest superfamily of gene-encoded plant antimicrobial peptides, which can act as molecular weapons to protect hosts from pathogen attacks. They exist either in a cyclic form as cyclotides or in a linear form as acyclotides. This study is focused on cyclotides, which are further sub-classified into Möbius and bracelet cyclotides. They share a signature core comprising a cyclic cystine knot formed by six cysteine residues, and this often gives the presumption that the same loops in all cyclotides are responsible for interactions with membranes. However, findings from an NMR spectroscopy experiment showed that different binding modes are adopted for Möbius and bracelet cyclotides. Therefore, this study employed molecular dynamics simulations to compare the different ways by which the two families of cyclotides interact with membrane-mimicking micelles. Consequently, analysis of the interaction interface has shown that loops 1, 2, 5, and 6 of kB2 were identified at the peptide-micelle interface, whereas loops 2 and 3 of cO2 were consistently in contact with the micelle surface. In addition, these simulations have discovered two configurational states for kB2, which were previously not demonstrated. More importantly, this study confirms that hydrophobic interactions largely govern cyclotide-membrane interactions.